Evaluation of a Diabetes Prevention Program Lifestyle Intervention in Older Adults: A Randomized Controlled Study in Three Senior/Community Centers of Varying Socioeconomic Status. Issue 2 (April 2018) - Kramer, M. Kaye; Vanderwood, Karl K.; Arena, Vincent C.; Miller, Rachel G.; Meehan, Rebecca; Eaglehouse, Yvonne L.; Schafer, Gerald; Venditti, Elizabeth M.; Kriska, Andrea M.
Purpose: The purpose of this study is to evaluate the feasibility and effectiveness of an adapted Diabetes Prevention Program (DPP) lifestyle program, DPP Group Lifestyle Balance (GLB), delivered in 3 economically diverse senior/community centers. Methods: The DPP-GLB was implemented in 3 senior/community centers in Allegheny County, PA. A 6-month delayed control intervention design was used. Participants were randomized to begin the DPP-GLB immediately (immediate) or after a 6-month delay (delayed). Adults (n = 134; mean age = 62.8 years) with BMI ≥24 kg/m 2 and prediabetes and/or the metabolic syndrome took part. Weight, physical activity (PA), and diabetes and cardiovascular disease (CVD) risk factors were assessed at 6, 12, and 18 months from baseline. Results: At 6 months, the immediate group demonstrated greater mean weight loss than the delayed control group as well as significantly greater improvements in PA, A1C, fasting insulin, and waist circumference. In pre-post analyses, both randomized groups showed similar success that was maintained at 18 months. Conclusions: The DPP-GLB delivered in economically diverse community centers was effective in this group of older adults. These findings support provision of coverage for prevention programs in older adults at risk for diabetes/CVD, which is important considering the large number of individuals who will be Medicare eligible in the near future.